2000
DOI: 10.1148/radiology.215.3.r00jn42910
|View full text |Cite
|
Sign up to set email alerts
|

Normal Lumbar Vertebrae: Anatomic, Age, and Sex Variance in Subjects at Proton MR Spectroscopy—Initial Experience

Abstract: Fifty-seven subjects underwent proton magnetic resonance (MR) spectroscopy of the second lumbar vertebra to evaluate single-voxel and multivoxel techniques. Measurements included lipid-to-water ratios, lipid fractions, and line width. These data provide information about vertebral fat content. There was an age-dependent linear increase in fat content and sex dependence. A higher fat concentration was found in men. The observed spectra provide a basis for future study to determine clinical utility of vertebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
90
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 33 publications
12
90
2
1
Order By: Relevance
“…The rate at which bone marrow conversion takes place is generally slower in the central compared with the peripheral skeleton (29). The fat content, which progresses gradually with a 7% increase per decade, reaches a balanced ratio of fat to hematopoietic marrow in the 50-year-old subject (30,31). Our study population was relatively elderly compared with the younger populations in the studies by Pache et al and Guggenberger et al However, further research is needed to determine optimal parameter settings for the reconstruction of noncalcium images under different circumstances.…”
Section: Musculoskeletal Imaging: Bone Marrow Edema In Vertebral Compmentioning
confidence: 99%
“…The rate at which bone marrow conversion takes place is generally slower in the central compared with the peripheral skeleton (29). The fat content, which progresses gradually with a 7% increase per decade, reaches a balanced ratio of fat to hematopoietic marrow in the 50-year-old subject (30,31). Our study population was relatively elderly compared with the younger populations in the studies by Pache et al and Guggenberger et al However, further research is needed to determine optimal parameter settings for the reconstruction of noncalcium images under different circumstances.…”
Section: Musculoskeletal Imaging: Bone Marrow Edema In Vertebral Compmentioning
confidence: 99%
“…Relative vertebral fat content can be estimated from the peak LWR. The fat fraction (FF) is derived from the formula: FF ϭ peak LWR/(peak LWR ϩ 1) (14). The area under the peak of the lipid or water signals was measured by the Lorentzian curve-fitting procedure.…”
Section: H Mrs Measurementsmentioning
confidence: 99%
“…Proton MR spectroscopy ( 1 H MRS) can analyze the contents of bone marrow components quantitatively (8 -11). The lipid and water contents of normal and aging bone marrow have been successfully evaluated by the 1 H MRS (12)(13)(14)(15). De Bisschop et al (12) evaluated the fat fraction of bone marrow by MR methods and found a systemic increase in measured fat percentage of about 7% per decade of age.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The water peak is originating mostly from red marrow, while the lipid peak arises mainly from yellow marrow . MRS has been used to illustrate the increase bone marrow fat content with age Chellinger et al 2000 ).…”
Section: Magnetic Resonance Imaging Of the Bone Marrowmentioning
confidence: 99%